2008
DOI: 10.1158/0008-5472.can-07-5767
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Melanoma Invasion by a Secreted Variant of Activated Leukocyte Cell Adhesion Molecule

Abstract: Activated leukocyte cell adhesion molecule (ALCAM/CD166/ MEMD), a marker of various cancers and mesenchymal stem cells, is involved in melanoma metastasis. We have exploited a secreted NH 2 -terminal fragment, sALCAM, to test the hypothesis that ALCAM coordinates tissue growth and cell migration. Overexpression of sALCAM in metastatic melanoma cells disturbed clustering of endogenous ALCAM and inhibited activation of matrix metalloproteinase-2 (MMP-2). Exposure of HT1080 fibrosarcoma cells to sALCAM similarly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 49 publications
6
58
0
Order By: Relevance
“…These results are in line with the fact that ALCAM is a cell-to-cell adhesion receptor known to play a major role in mediating the interactions between endothelial and tumor or immune cells during transendothelial migration (39)(40)(41). Moreover, ALCAM was found to be involved in cell movement (42) and in the conversion of the prometastatic pro-MMP-2 to its active form in malignancy (43). On the other hand, modulations of integrin levels were associated with various metastatic phenotypes (35,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 74%
“…These results are in line with the fact that ALCAM is a cell-to-cell adhesion receptor known to play a major role in mediating the interactions between endothelial and tumor or immune cells during transendothelial migration (39)(40)(41). Moreover, ALCAM was found to be involved in cell movement (42) and in the conversion of the prometastatic pro-MMP-2 to its active form in malignancy (43). On the other hand, modulations of integrin levels were associated with various metastatic phenotypes (35,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 74%
“…Significantly, the fraction of ALCAM-positive lesions increases according to invasiveness (Clark level) and thickness (Breslow index) of the melanocytic tumor (8). It was shown that any interference with ALCAM function affects melanoma cell movement and invasion (9,10) and that ALCAM triggers MMP2 and MMP14 activity (11). However, it is still not known how ALCAM overexpression is induced in melanomas and how it coordinates metastasis formation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ALCAM expression has been implicated in apoptosis [5], angiogenesis [6], migration, and invasion [7] of various cell types. Concerning the role of ALCAM in human cancer, the results are partly controversial: In many tumors, ALCAM expression is associated with high invasive and metastatic potential and poor prognosis, i.e., in melanoma [8,9], colorectal cancer [10], oral cancer [11], pancreatic carcinoma [12], and esophageal carcinoma [13].…”
Section: Introductionmentioning
confidence: 99%